2012
DOI: 10.1371/journal.pone.0052571
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Antibodies to a Panel of Plasmodium falciparum Specific Antigens and Response to Sub-Optimal Antimalarial Therapy in Kampala, Uganda

Abstract: BackgroundAntibodies are important in the control of blood stage Plasmodium falciparum infection. It is unclear which antibody responses are responsible for, or even associated with protection, partly due to confounding by heterogeneous exposure. Assessment of response to partially effective antimalarial therapy, which requires the host to assist in clearing parasites, offers an opportunity to measure protection independent of exposure.MethodsA cohort of children aged 1–10 years in Kampala, Uganda were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 37 publications
(47 reference statements)
2
12
0
Order By: Relevance
“…For example, presence of antibodies against Rh2 and AMA1 in ELISAs correlated to invasion for both tested clinical isolates, and antibodies against AMA1 in ELISAs also correlated to affinity SPR results, indicating that this protein might be targeted by functionally important, high-affinity antibodies that could contribute to protection from severe malaria. Our findings are consistent with recent studies from Uganda (76,77) that showed a strong association between antibodies against AMA1 and protection against malaria. Other antigens, such as MSP1, showed no difference in antibody levels between uncomplicated and severe malaria and did not show any correlations with invasion.…”
Section: Discussionsupporting
confidence: 93%
“…For example, presence of antibodies against Rh2 and AMA1 in ELISAs correlated to invasion for both tested clinical isolates, and antibodies against AMA1 in ELISAs also correlated to affinity SPR results, indicating that this protein might be targeted by functionally important, high-affinity antibodies that could contribute to protection from severe malaria. Our findings are consistent with recent studies from Uganda (76,77) that showed a strong association between antibodies against AMA1 and protection against malaria. Other antigens, such as MSP1, showed no difference in antibody levels between uncomplicated and severe malaria and did not show any correlations with invasion.…”
Section: Discussionsupporting
confidence: 93%
“…2 , was significant for 50 % of the biomarkers. These results are in agreement with several studies involving sulfadoxine–pyrimethamine or amodiaquine treatment, showing a significant association of higher levels of antibodies to GLURP [ 47 ], AMA1 [ 48 ] and MSP1 [ 49 ] antigens with a lower risk of treatment failure. Another study showed the contribution of antibodies to the Ring Erythrocyte Surface antigen to the therapeutic response in Thai patients treated with artesunate [ 50 ].…”
Section: Discussionsupporting
confidence: 92%
“…A further two studies investigated the association between P. falciparum antibody responses and chloroquine treatment failure (CQ) [ 22 , 26 ] (Table 2 ). The included studies reported total IgG responses to antigens P. falciparum merozoite antigens (MSP1 [ 23 , 27 ], MSP1-19 [ 22 , 24 26 ], MSP1 Block 2 proteins [ 23 ], MSP2 [ 24 , 28 ], MSP3 [ 22 , 24 ], EBA-175 [ 27 ], AMA-1 [ 24 , 26 28 ]) and antigens expressed on the surface of Pf -IE (VSAs [ 27 , 28 ], RESA [ 29 ],), as well as schizont extract [ 27 ]. Two studies reported IgG responses to the glutamate rich protein (GLURP) [ 22 , 24 ], which is expressed in multiple parasite life stages but was analysed with merozoite specific responses (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%